How Do Young Adults Develop Preferences Towards Clothing Retail Stores? - Kuruppu, Asita (2012)
Executive Summary This dissertation primarily explores how young adults develop preferences towards clothing retail stores. It also aims to identify if a difference exists in preferences between males and females. The Two stores selected for participants to base their preferences on were French Connection and All Saints. Literature drawn from consumer behaviour which consists of self-concept, symbolic consumption, and store image and reference groups was used for this dissertation. The results of this study showed that young adults did heighten their preferences for clothing stores as a result of the concepts derived from the literature. An interesting finding was that some young adults attached the same symbolic meanings which they attached to clothes to their favourite clothing stores. Furthermore it was found that young adults prefer stores which are congruent to their ideal and actual self-concepts and they avoided stores which were not consistent to their identities and self-image. Although there was evidence of reference group influence the participants primarily used their own judgement and evaluation towards clothing stores. This could be because the young adults in this study were found to be individualistic and valued creating their own identities rather than conforming to others. The most important component of store image was found to be employees and store atmosphere. The quality of merchandise and price of merchandise was also considered important. The dissertation concludes with marketing implications for retail stores and managers. The research limitations of the study are also discussed.